2021
DOI: 10.1136/bmjopen-2020-044706
|View full text |Cite
|
Sign up to set email alerts
|

Uneven state distribution of homicides in Brazil and their effect on life expectancy, 2000–2015: a cross-sectional mortality study

Abstract: ObjectiveTo determine cause-specific and age-specific contributions to life expectancy changes between 2000 and 2015, separately by state and sex in Brazil, with a focus on homicides.DesignRetrospective cross-sectional demographic analysis of mortality.Setting and populationBrazilian population by age, sex and state from 2000 to 2015.Main outcome measureUsing mortality data from the Brazilian Mortality Information System and population estimates from the National Statistics Office, we used death distribution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…Homicide mortality for males was higher than for females in all age groups, as in other homicide studies worldwide 9,3840 and in Mexico. 17,41,42 Premature homicide mortality in 2020 was more than eight times higher for men compared to women in Mexico, while the global homicide rate for the male population is roughly four times the rate for females.…”
Section: Discussionsupporting
confidence: 83%
“…Homicide mortality for males was higher than for females in all age groups, as in other homicide studies worldwide 9,3840 and in Mexico. 17,41,42 Premature homicide mortality in 2020 was more than eight times higher for men compared to women in Mexico, while the global homicide rate for the male population is roughly four times the rate for females.…”
Section: Discussionsupporting
confidence: 83%
“…Black men from the urban periphery with criminal records [20]. At the national level, there was a migration of crime from large urban centers to other regions of the country, where social inequality, access to firearms, drug trafficking, and alcohol and drug abuse contributed to Brazil presenting a mortality risk ten times higher than that of developed countries [5,7]. In the study area, the increase in female homicides followed that of male homicides, with clearer trends in adolescents aged 15 to 19 years, predominantly those of non-White color and linked to criminal activities.…”
Section: Plos Onementioning
confidence: 99%
“…A study of 24 countries in the region revealed that this type of violence affects 14% to 60% of the female population of childbearing age (15-49 years). Other studies have shown a relationship between increased urban violence and elevated gender violence, especially where great socioeconomic inequality and the influence of organized crime and drug trafficking exist [5,7,38]. In Brazil, the prevalence is that one in seven women (14%-17%) may be a victim of intimate partner violence at some point in life [4].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations